2001
DOI: 10.1109/20.950853
|View full text |Cite
|
Sign up to set email alerts
|

High magnetization exchange-couple double-layer TbFeCo for magnetic flux reading optical recording

Abstract: High magnetization (Mr) and enhanced coercivity magneto-optical (MO) recording media TbFeCo (TFC) were investigated for hybrid magnetic flux reading/optical recording due to their large magnetic flux. To increase the stability of high Mr TFC media, dual-layer disks composed of TM-rich readout layer with saturation magnetization (Ms) = 370 emu/cm 3 and RE-rich memory layer were fabricated. Coercivity and interface energy between double layers as a function of active layer thickness were examined. By simulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This is due to the exchange interaction between the ferromagnetic and ferrimagnetic phase at their interface. Such exchange bias fields have been observed in case of many ferromagnet/ferrimagnet interfaces like γ-Fe 2 O 3 /Fe [14] and Co/TbFe [15]. The values of magnetic moment per manganese atom in In 1− Mn Sb alloys (for 0 2), determined from saturation magnetisation at T = 5 K, are in the (2.07-3.28) µ B range (Tab.…”
Section: Magnetic Measurementsmentioning
confidence: 98%
“…This is due to the exchange interaction between the ferromagnetic and ferrimagnetic phase at their interface. Such exchange bias fields have been observed in case of many ferromagnet/ferrimagnet interfaces like γ-Fe 2 O 3 /Fe [14] and Co/TbFe [15]. The values of magnetic moment per manganese atom in In 1− Mn Sb alloys (for 0 2), determined from saturation magnetisation at T = 5 K, are in the (2.07-3.28) µ B range (Tab.…”
Section: Magnetic Measurementsmentioning
confidence: 98%
“…1 Assuming the effective magnetization vector of the layer has a tilted angle f with respect to the surface normal and the ratio of XMCD signal at sample rotation 0 and 180 is k; then the tilted angle f equals to ½ð1 À kÞsinð25 Þ=½ð1 þ kÞcosð25 Þ: [6]. One consequence of such interface spin reorientation is the observation of exchange bias [7] or change of coercivity as found for this case [8]. Fig.…”
mentioning
confidence: 80%
“…The large interface wall energy is owing to the spin moments in the interface between the FePt layer and Tb 29.6 Co 70.4 layer are not fully compensated. Lin et al [23] had found that the uncompensated interface will cause high interface wall energy. Moreover, this large interface wall energy may be due to large magnetic magnetocrystalline anisotropy (Ku) of L1 0 FePt layer.…”
Section: Article In Pressmentioning
confidence: 99%